Taiwan: From “World-Class” to Socially Responsible - Lo, William Yat Wai (International Higher Education, 2019)
A new policy initiative called the Higher Education Sprout Project was launched in Taiwan in 2018. This project highlights social responsibility as a new key performance indicator that the government uses to monitor the performance of universities. This initiative reveals a reorientation of higher education policy that represents a shift from an outward-looking strategy to a relatively inward-looking approach, and exemplifies the relevance of local politics to higher education policy making.